Dietary Folate and Reproductive Success Among Women Undergoing Assisted Reproduction - Gaskins, Audrey J. (2014)
OBJECTIVE: To evaluate prospectively the associations of folate with assisted reproductive technology outcomes within a U.S. population. METHODS: This analysis included women (n=232) in a prospective cohort study at the Massachusetts General Hospital Fertility Center. Diet was assessed before assisted reproductive technology treatment using a validated food frequency questionnaire. Intermediate and clinical endpoints of ART were abstracted from medical records. Generalized linear mixed models with random intercepts to account for multiple cycles per woman were used to evaluate the association of folate intake with ART outcomes adjusting for calorie intake, age, BMI, race, smoking status, infertility diagnosis, and protocol type. RESULTS: Among the 232 women (median age=35.2 years, median folate intake=1,778 μg/day), higher folate intake was associated with higher rates of implantation, clinical pregnancy, and live birth. The adjusted percentage (95% CI) of initiated assisted reproductive technology cycles resulting in a live birth for women in increasing quartiles of folate intake were 30% (21, 42%), 47% (35, 59%), 42% (30, 35%) and 56% (43, 67%)(P-trend=0.01). Live birth rates were 20% (8, 31%) higher among women in the highest quartile of supplemental folate intake (>800μg/day) than among women in the lowest quartile (<400μg/day). Higher supplemental folate intake was associated with higher fertilization rates and lower cycle failure rates before embryo transfer (P-trend=0.03 and 0.02). CONCLUSIONS: Higher intake of supplemental folate was associated with higher live birth rates after assisted reproductive technology treatment.